Sweetening Awareness: A Playful Interaction With Sugars in Food for Children - Mueller, Marco (Auckland University of Technology, 2018)
The aim of this project was to create a tool for six to eight-year-old children that allows them to learn about sugars in food in an easy and entertaining way. Sugars are present in a wide range of food products and coincidentally, health issues potentially related to sugars (like diabetes type 2, obesity, tooth decay or cardiovascular disease) are on the rise; not only in adults but alarmingly in children as well. Although several ways to learn about the content of a food item exist, they usually are rather complex, not made for young children or do not feature interactive elements that could invoke motivation or fun. Considering that many unhealthy products target young children specifically, a tool for a younger audience could therefore be a valuable addition. Multiple existing approaches to educate children about sugars and nutrition were analysed to identify the elements for a new tool to create awareness. The resulting prototype, in the form of an app for smartphones, was given to school children of the targeted age group to play and interact with. The app allowed participants to retrieve information about a product’s sugar content by scanning its packaging’s barcode. The experience was enhanced by adding gamification elements that tried to capture the participants’ attention and motivation. The results of this case study showed that young children are indeed able to interact with food related information if presented in an adequate way. Subsequently, most participants declined to include items high in sugars within the app and, instead, opted for “healthier” alternatives once they learnt about the actual sugar content of a product. While this behaviour showed that awareness about sugars in food could be established, more research should be undertaken to understand how long this awareness can be sustained, after children interacted with this app.
Keywords: Educational app for children; Creating awareness in children; Sugar and kids; Barcode food scanner for children; Interactive method to create awareness; Colab; Creative technologies